THE ROLE OF ORGANISATIONAL COMMITMENT AS A MEDIATING VARIABLE BETWEEN JOB COMPETENCE AND EMPLOYEE PERFORMANCE - Acang Nurachman; Edi Sugiono; Suryono Efendi (International Journal of Social Science, 2025)
This study aims to examine the role of organizational commitment as a mediating variable between work competence and employee performance at the Indonesian Agricultural Quarantine Agency. In a competitive business environment, human resource management becomes a key factor in achieving organizational excellence. Work competence is considered an important factor in enhancing performance, yet employees’ emotional attachment to the organization also plays a vital role in optimizing their contributions. The study adopts a quantitative approach with explanatory research methods and employs Partial Least Squares (PLS) analysis to test the relationships among variables. The results show that work competence significantly influences organizational commitment (coefficient 0.762, T statistic 13.579) and employee performance (coefficient 0.417, T statistic 10.175). Organizational commitment also has a significant effect on employee performance (coefficient 0.578, T statistic 14.550). Moreover, organizational commitment is proven to be a significant mediating variable in the relationship between work competence and employee performance (coefficient 0.440, T statistic 8.909). These findings are supported by social exchange theory and the psychological contract, as well as prior studies such as Meyer and Allen (1991) and Mowday et al. (1979), although other research has shown varying results depending on organizational context. The study concludes that improving work competence must be accompanied by strategies to strengthen organizational commitment in order to achieve optimal employee performance. The practical implication is that organizations should create a supportive work environment, provide recognition for employee competence, and foster strong emotional bonds with employees.